Bridging the energy access divide for sustainable development in South Asia: Policies and prospects in Nepal - Dhakal, Subas P.; Mahmood, M.; Bogati, R. (2018)
Bridging the energy access divide is critical for meeting Nepal's social and economic development objectives. Under the assumption that there are fertile opportunities for linking energy policy and market prospects, this paper explores the central question: 'to what extent is the current policy environment in Nepal conducive to the uptake of solar energy at the household level?' The paper makes use of an exploratory research approach to data analyses in order to address the research question. The findings reveal that the country's renewable energy market is still in its infancy. Although donor-driven subsidy policy has been successful in promoting the uptake of solar energy, exclusivity of subsidy mechanisms coupled with the lack of cross-sectoral policy harmony are hindering the uptake of solar energy. The paper ends with a discussion on the need for a market-centric impetus to facilitate a renewable energy sector in Nepal.